INOVASI MODEL KOMUNIKASI KRISIS BERBASIS KOMUNITAS - Bachtiar, Willy; Febri Astuti, Vivien; Marithasari, Harries (Jurnal Sains Indonesia, 2021)
Research entitled Community-Based Crisis Communication Model Innovation (Case Study of Disaster and Pandemic Mitigation in Bogor City and District by the BORAC Community). This study aims to formulate a community-based crisis innovation model that is able to bridge the fulfillment of information needs, education, preparedness, empowerment of affected communities and social aspects. This study provides an overview of communication science applied to Disaster Mitigation, especially building a community-based crisis communication model during disasters and pandemics. This study used a qualitative descriptive method and a collection method with interviews, observations, and literature studies. The results showed that the BORAC Community succeeded in carrying out crisis communication and disaster mitigation programs including socializing information on COVID19 mitigation, local heroes programs, implementing programs such as Eid Gifts, Fasting Coupons, and Replanting. The results of sharing these activities have changed people's attitudes ranging from cognitive, affective, and psychomotor so that people have high preparedness in dealing with disasters and have high resilience in the event of a disaster. This model of crisis communication can be adopted by other regions.